Round‐the‐Clock Photocatalytic Hydrogen Production with High Efficiency by a Long‐Afterglow Material. Issue 5 (27th December 2018) - Cui, Guanwei; Yang, Xiuli; Zhang, Yujia; Fan, Yaqi; Chen, Ping; Cui, Hongyu; Liu, Yan; Shi, Xifeng; Shang, Qiaoyan; Tang, Bo
Abstract: Long afterglow materials can store and release light energy after illumination. A brick‐like, micrometer‐sized Sr2 MgSi2 O7 :Eu 2+, Dy 3+ long‐afterglow material is used for hydrogen production by the photocatalytic reforming of methanol under round‐the‐clock conditions for the first time, achieving a solar‐to‐hydrogen (STH) conversion efficiency of 5.18 %. This material is one of the most efficient photocatalysts and provides the possibility of practical use on a large scale. Its remarkable photocatalytic activity is attributed to its unique carrier migration path and large number of lattice defects. These findings expand the application scope of long afterglow materials and provide a new strategy to design efficient photocatalysts by constructing trap levels that can prolong carrier lifetimes. Abstract : A brick‐like, micrometer‐sized Sr2 MgSi2 O7 :Eu 2+, Dy 3+ long afterglow material is used for hydrogen production via the photocatalytic reforming of methanol under round‐the‐clock conditions, achieving a solar‐to‐hydrogen (STH) conversion efficiency of 5.18 %. This material is one of the most efficient photocatalysts and provides the possibility of practical use on a large scale.